2005
DOI: 10.1002/pssa.200521141
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen precipitation in neutron‐irradiated Czochralski silicon annealed at elevated temperature

Abstract: The effects of vacancies introduced by neutron-irradiation on oxygen precipitation at elevated temperatures in Czochralski (CZ) silicon have been investigated. In comparison with noirradiated CZ silicon, the neutron-irradiated CZ silicon exhibits stronger oxygen precipitation at 1050 °C or 1150 °C due to the existence of supersaturated vacancies in the bulk. Moreover, it is proved that the oxygen out-diffusion at high temperature is not enhanced by the supersaturated vacancies induced by neutron-irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Oxygen precipitation processes are known to be sensitive to the presence of other impurities, especially carbon 6,7 as well as radiationproduced defects. 8,9 Besides oxygen, carbon is another important impurity being sometimes present in Cz-Si crystals in substantial concentrations. Normally, carbon atoms are substitutional in the Si lattice and they are electrically inactive.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen precipitation processes are known to be sensitive to the presence of other impurities, especially carbon 6,7 as well as radiationproduced defects. 8,9 Besides oxygen, carbon is another important impurity being sometimes present in Cz-Si crystals in substantial concentrations. Normally, carbon atoms are substitutional in the Si lattice and they are electrically inactive.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that in the irradiated material C suppresses the formation of spheroidal precipitates although it enhances the platelet the O and C impurities, including divacancies, oxygenvacancy and oxygen-carbon complexes [9,12,15]. There are interactions between the two kinds of defects and in particular radiation defects usually affect the growth and evolution of precipitates [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen does not normally occupy a substitutional site, however, in irradiated crystals the mobile vacancy can be trapped at the O i atom and forms the vacancy-oxygen complex. [4,5] Electron irradiation of Czochralski-grown silicon (Cz-Si) leads to the formation of oxygen-vacancy complexes, so-called A-centres, where a single oxygen atom occupies a vacant site, with a slight off-centre displacement. The A-centre has been studied extensively by many experimental techniques.…”
Section: Introductionmentioning
confidence: 99%